MANIFESTACIONES ORALES EN PACIENTES CON ARTRITIS REUMATOIDEA QUE ASISTEN AL INSTITUTO DE REHABILITACIÓN Y REUMATOLOGIA DE BUCARAMANGA (2018)
Purpose: To determine the orofacial and bucodental profile of patients with Rheumatoid Arthritis according to the development of the disease.Material and methods: Forty eight individuals with Rheumatoid Arthritis were analyzed. The prevalence of alterations in the facial exam, temporomandibular joint (TMJ) intraoral exam, COP index, periodontal condition (CPITN), and radiographic interpretation were determined.Results: In the group studied, 77.08% were female and their average mean age was 48.7% years old. The scalp showed the highest frequency of abnormality, 22.9%; the most frequent TMJ alteration was pain, 60.42% which was 41.67% bilateral; oral mucosa showed the greatest number of lesions (37.5%); the periodontal condition was 50% of the population had periodontal pockets of 4 to 5 mm in the presence of subgingival calculus. Radiographically, 19.05% had thin roots; 42.86% had posterior hypercementosis; 11.9% reduced TM joint space.Conclusions: The alterations of the oral mucosa reflect an elevated prevalence of red lesions. Furthermore, these patients have a greater risk of developing periodontal disease.